Legal Strategies in Childhood Obesity Prevention: Workshop Summary - Institute of Medicine (The National Academies Press, 2011)
Since 1980, childhood obesity rates have more than tripled in the United States. Recent data show that almost one-third of children over 2 years of age are already overweight or obese. While the prevalence of childhood obesity appears to have plateaued in recent years, the magnitude of the problem remains unsustainably high and represents an enormous public health concern. All options for addressing the childhood obesity epidemic must therefore be explored. In the United States, legal approaches have successfully reduced other threats to public health, such as the lack of passive restraints in automobiles and the use of tobacco. The question then arises of whether laws, regulations, and litigation can likewise be used to change practices and policies that contribute to obesity. On October 21, 2010, the Institute of Medicine (IOM) held a workshop to bring together stakeholders to discuss the current and future legal strategies aimed at combating childhood obesity. Legal Strategies in Childhood Obesity Prevention summarizes the proceedings of that workshop. The report examines the challenges involved in implementing public health initiatives by using legal strategies to elicit change. It also discusses circumstances in which legal strategies are needed and effective. This workshop was created only to explore the boundaries of potential legal approaches to address childhood obesity, and therefore, does not contain recommendations for the use of such approaches.

Leading Health Indicators for Healthy People 2020: Letter Report - Institute of Medicine (The National Academies Press, 2011)
For the past three decades, the Department of Health and Human Services (HHS) has issued a national agenda aimed at improving the health of all Americans over each 10-year span. Under each of these Healthy People initiatives, HHS established health targets and monitored how well people were reaching them over time. In response to a request from the Department of Health and Human Services (HHS), the Institute of Medicine (IOM) established the Committee on Leading Health Indicators for Healthy People 2020 to develop and recommend 12 indicators and 24 objectives for consideration by HHS for guiding a national health agenda and for consideration for inclusion in Healthy People 2020. The work of the committee built upon the 1999 IOM report, Leading Health Indicators for Healthy People 2010, and on the work of the Committee on the State of the USA Health Indicators. Leading Health Indicators for Healthy People 2020 lays out the proposed agenda for the current decade, which will end in 2020.

For the Public's Health: Revitalizing Law and Policy to Meet New Challenges - Institute of Medicine (The National Academies Press, 2011)
The Robert Wood Johnson Foundation asked the Institute of Medicine (IOM) to examine three topics in relation to public health: measurement, the law, and funding. IOM prepared a three book series-one book on each topic-that contain actionable recommendations for public health agencies and other stakeholders that have roles in the health of the U.S population. For the Public's Health: Revitalizing Law and Policy to Meet New Challenges is the second in the For the Public Health's Series, and reflects on legal and public policy reform on three levels: first, laws that establish the structure, duties, and authorities of public health departments; second, the use of legal and policy tools to improve the public's health; and third, the health effects of laws and policies from other sectors in and outside government. The book recommends that states enact legislation with appropriate funding to ensure that all public health departments have the mandate and the capacity to effectively deliver the Ten Essential Public Health Services. The book also recommends that states revise their laws to require public health accreditation for state and local health departments through the Public Health Accreditation Board accreditation process. The book urges government agencies to familiarize themselves with the public health and policy interventions at their disposal that can influence behavior and more importantly change conditions-social, economic, and environmental-to improve health. Lastly, the IOM encourages government and private-sector stakeholders to consider health in a wide range of policies (a health in all policies approach) and to evaluate the health effects and costs of major legislation. This book, as well as the other two books in the series, is intended to inform and help federal, state, and local governments, public health agencies, clinical care organizations, the private sector, and community-based organizations.

Clinical Preventive Services for Women: Closing the Gaps - Institute of Medicine (The National Academies Press, 2011)
Women suffer disproportionate rates of chronic disease and disability from some conditions, and often have high out-of-pocket health care costs. The passage of the Patient Protection and Affordable Care Act of 2010 (ACA) provides the United States with an opportunity to reduce existing health disparities by providing an unprecedented level of population health care coverage. The expansion of coverage to millions of uninsured Americans and the new standards for coverage of preventive services that are included in the ACA can potentially improve the health and well-being of individuals across the United States. Women in particular stand to benefit from these additional preventive health services. Clinical Preventive Services for Women reviews the preventive services that are important to women's health and well-being. It recommends that eight preventive health services for women be added to the services that health plans will cover at no cost. The recommendations are based on a review of existing guidelines and an assessment of the evidence on the effectiveness of different preventive services. The services include improved screening for cervical cancer, sexually transmitted infections, and gestational diabetes; a fuller range of contraceptive education, counseling, methods, and services; services for pregnant women; at least one well-woman preventive care visit annually; and screening and counseling for interpersonal and domestic violence, among others. Clinical Preventive Services for Women identifies critical gaps in preventive services for women as well as measures that will further ensure optimal health and well-being. It can serve as a comprehensive guide for federal government agencies, including the Department of Health and Human Services and the Center for Disease Control and Prevention; state and local government agencies; policy makers; health care professionals; caregivers, and researchers.

The National Cancer Policy Summit: Opportunities and Challenges in Cancer Research and Care - Institute of Medicine (The National Academies Press, 2011)
Many ongoing changes are likely to have an impact on cancer research and care. For example, technological advances are rapidly changing the way cancer research is conducted, and the recently passed healthcare reform legislation has many implications for cancer care. Technological advances are altering the way cancer research is conducted and cancer care is delivered, and the recently passed healthcare reform legislation has many implications for cancer care. There is a growing emphasis on molecularly targeted therapies, information technology (IT), and patient-centered care, and clinical cancer research has become a global endeavor. At the same time, there are concerns about shrinking research budgets and escalating costs of cancer care. Considering such changes, the National Cancer Policy Forum (NCPF) of the Institute of Medicine held a National Cancer Policy Summit on October 25, 2010. The Summit convened key leaders in the cancer community to identify and discuss the most pressing policy issues in cancer research and cancer care. The National Cancer Policy Summit: Opportunities and Challenges in Cancer Research and Care is a summary of the summit. The report explores policy issues related to cancer research, the implementation of healthcare reform, delivery of cancer care, and cancer control and public health needs. Expert participants suggested many potential actions to provide patient-centered cancer care, to foster more collaboration, and to achieve other goals to improve research and care.

State and Local Policy Initiatives to Reduce Health Disparities: Workshop Summary - Institute of Medicine (The National Academies Press, 2011)
Although efforts to reduce health disparities receive attention at the national level, information on the successes of state and local efforts are often not heard. On May 11, 2009, the Institute of Medicine held a public workshop to discuss the role of state and local policy initiatives to reduce health disparities. The workshop brought together stakeholders to learn more about what works in reducing health disparities and ways to focus on localized efforts when working to reduce health disparities.

Advancing Oral Health in America - Institute of Medicine (The National Academies Press, 2011)
Though it is highly preventable, tooth decay is a common chronic disease both in the United States and worldwide. Evidence shows that decay and other oral diseases may be associated with adverse pregnancy outcomes, respiratory disease, cardiovascular disease, and diabetes. However, individuals and many health care professionals remain unaware of the risk factors and preventive approaches for many oral diseases. They do not fully appreciate how oral health affects overall health and well-being. In Advancing Oral Health in America, the Institute of Medicine (IOM) highlights the vital role that the Department of Health and Human Services (HHS) can play in improving oral health and oral health care in the United States. The IOM recommends that HHS design an oral health initiative which has clearly articulated goals, is coordinated effectively, adequately funded and has high-level accountability. In addition, the IOM stresses three key areas needed for successfully maintaining oral health as a priority issue: strong leadership, sustained interest, and the involvement of multiple stakeholders from both the public and private sectors. Advancing Oral Health in America provides practical recommendations that the Department of Health and Human Services can use to improve oral health care in America. The report will serve as a vital resource for federal health agencies, health care professionals, policy makers, researchers, and public and private health organizations.

Promoting Health Literacy to Encourage Prevention and Wellness: Workshop Summary - Institute of Medicine (The National Academies Press, 2011)
Health literacy has been shown to affect health outcomes. The use of preventive services improves health and prevents costly health care expenditures. Several studies have found that health literacy makes a difference in the extent to which populations use preventive services. On September 15, 2009, the Institute of Medicine Roundtable on Health Literacy held a workshop to explore approaches to integrate health literacy into primary and secondary prevention. Promoting Health Literacy to Encourage Prevention and Wellness serves as a factual account of the discussion that took place at the workshop. The report describes the inclusion of health literacy into public health prevention programs at the national, state, and local levels; reviews how insurance companies factor health literacy into their prevention programs; and discusses industry contributions to providing health literate primary and secondary prevention.

A Nationwide Framework for Surveillance of Cardiovascular and Chronic Lung Diseases - Institute of Medicine (The National Academies Press, 2011)
Chronic diseases are common and costly, yet they are also among the most preventable health problems. Comprehensive and accurate disease surveillance systems are needed to implement successful efforts which will reduce the burden of chronic diseases on the U.S. population. A number of sources of surveillance data2014including population surveys, cohort studies, disease registries, administrative health data, and vital statistics2014contribute critical information about chronic disease. But no central surveillance system provides the information needed to analyze how chronic disease impacts the U.S. population, to identify public health priorities, or to track the progress of preventive efforts. A Nationwide Framework for Surveillance of Cardiovascular and Chronic Lung Diseases outlines a conceptual framework for building a national chronic disease surveillance system focused primarily on cardiovascular and chronic lung diseases. This system should be capable of providing data on disparities in incidence and prevalence of the diseases by race, ethnicity, socioeconomic status, and geographic region, along with data on disease risk factors, clinical care delivery, and functional health outcomes. This coordinated surveillance system is needed to integrate and expand existing information across the multiple levels of decision making in order to generate actionable, timely knowledge for a range of stakeholders at the local, state or regional, and national levels. The recommendations presented in A Nationwide Framework for Surveillance of Cardiovascular and Chronic Lung Diseases focus on data collection, resource allocation, monitoring activities, and implementation. The report also recommends that systems evolve along with new knowledge about emerging risk factors, advancing technologies, and new understanding of the basis for disease. This report will inform decision-making among federal health agencies, especially the Department of Health and Human Services; public health and clinical practitioners; non-governmental organizations; and policy makers, among others.

The Science of Adolescent Risk-Taking: Workshop Report - Institute of Medicine; National Research Council (The National Academies Press, 2011)
Adolescence is a time when youth make decisions, both good and bad, that have consequences for the rest of their lives. Some of these decisions put them at risk of lifelong health problems, injury, or death. The Institute of Medicine held three public workshops between 2008 and 2009 to provide a venue for researchers, health care providers, and community leaders to discuss strategies to improve adolescent health.

For the Public's Health: The Role of Measurement in Action and Accountability - Institute of Medicine (The National Academies Press, 2011)
Despite having the costliest medical care delivery system in the world, Americans are not particularly healthy. Recent international comparisons show that life expectancy in the U.S. ranks 49th among all nations, and infant mortality rates are higher in the U.S. than in many far less affluent nations. While these statistics are alarming, the bigger problem is that we do not know how to reverse this trend. Our lack of knowledge is due in large part to significant inadequacies in the health system for gathering, analyzing, and communicating health information about the population. To inform the public health community and all other sectors that contribute to population health, For the Public's Health: The Role of Measurement in Action and Accountability reviews current approaches for measuring the health of individuals and communities and creates a roadmap for future development. This book, the first of three in a series, focuses on data and measurement-not as ends in themselves, but rather tools to inform the myriad programs, policies, and processes developed or undertaken by governmental public health agencies and their many partners in the health system. For the Public's Health seeks to reinstate the proper and evidence-based understanding of health as not merely the result of medical or clinical care but the result of the sum of what we do as a society to create the conditions in which people can be healthy. To achieve this goal, the book suggests changes in the processes, tools, and approaches used to gather information about health outcomes and their determinants. The book also recommends developing an integrated and coordinated system in which all parties-including governmental and private sector partners at all levels-have access to timely and meaningful data to help foster individual and community awareness and action.

Sustainable Airport Construction Practices - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2011)
TRB2019s Airport Cooperative Research Program (ACRP) Report 42: Sustainable Airport Construction Practices explores a set of best practices, methods, procedures, and materials that if implemented during construction may have a sustainable, positive economic, operational, environmental, or social effect.The report includes the collection of sustainable airport construction practices in a searchable, filterable spreadsheet format on a CD-ROM, which is packaged with the report.The CD-ROM included as part of ACRP Report 42 is also available for download from TRB2019s website as an ISO image. Links to the ISO image and instructions for burning a CD-ROM from an ISO image are provided below.Help on Burning an .ISO CD-ROM ImageDownload the .ISO CD-ROM Image(Warning: This is a large file that may take some time to download using a high-speed connection.)CD-ROM Disclaimer - This software is offered as is, without warranty or promise of support of any kind either expressed or implied. Under no circumstance will the National Academy of Sciences or the Transportation Research Board (collectively 201cTRB2019) be liable for any loss or damage caused by the installation or operations of this product. TRB makes no representation or warrant of any kind, expressed or implied, in fact or in law, including without limitation, the warranty of merchantability or the warranty of fitness for a particular purpose, and shall not in any case be liable for any consequential or special damages.

The Health of Lesbian, Gay, Bisexual, and Transgender People: Building a Foundation for Better Understanding - Institute of Medicine (The National Academies Press, 2011)
At a time when lesbian, gay, bisexual, and transgender individuals2014often referred to under the umbrella acronym LGBT2014are becoming more visible in society and more socially acknowledged, clinicians and researchers are faced with incomplete information about their health status. While LGBT populations often are combined as a single entity for research and advocacy purposes, each is a distinct population group with its own specific health needs. Furthermore, the experiences of LGBT individuals are not uniform and are shaped by factors of race, ethnicity, socioeconomic status, geographical location, and age, any of which can have an effect on health-related concerns and needs. The Health of Lesbian, Gay, Bisexual, and Transgender People assesses the state of science on the health status of LGBT populations, identifies research gaps and opportunities, and outlines a research agenda for the National Institute of Health. The report examines the health status of these populations in three life stages: childhood and adolescence, early\/middle adulthood, and later adulthood. At each life stage, the committee studied mental health, physical health, risks and protective factors, health services, and contextual influences. To advance understanding of the health needs of all LGBT individuals, the report finds that researchers need more data about the demographics of these populations, improved methods for collecting and analyzing data, and an increased participation of sexual and gender minorities in research. The Health of Lesbian, Gay, Bisexual, and Transgender People is a valuable resource for policymakers, federal agencies including the National Institute of Health (NIH), LGBT advocacy groups, clinicians, and service providers.

Health Literacy Implications for Health Care Reform: Workshop Summary - Institute of Medicine (The National Academies Press, 2011)
Health literacy is the degree to which one can understand and make decisions based on health information. Nearly 90 million adults in the United States have limited health literacy. While poor health literacy spans all demographics, rates of low health literacy are disproportionately higher among those with lower socioeconomic status, limited education, or limited English proficiency, as well as among the elderly and individuals with mental or physical disabilities. Studies have shown that there is a correlation between low health literacy and poor health outcomes. In 2010, President Obama signed the Affordable Care Act designed to extend access to health care coverage to millions of Americans who have been previously uninsured. Many of the newly eligible individuals who should benefit most from the ACA, however, are least prepared to realize those benefits as a result of low health literacy. They will face significant challenges understanding what coverage they are eligible for under the ACA, making informed choices about the best options for themselves and their families, and completing the enrollment process. Health Literacy Implications for Health Care Reform explores opportunities to advance health literacy in association with the implementation of health care reform. The report focuses on building partnerships to advance the field of health literacy by translating research findings into practical strategies for implementation, and on educating the public, press, and policymakers regarding issues of health literacy.

Generating Evidence for Genomic Diagnostic Test Development: Workshop Summary - Institute of Medicine (The National Academies Press, 2011)
Ten years after the sequencing of the human genome, scientists have developed genetic tests that can predict a person's response to certain drugs, estimate the risk of developing Alzheimer's disease, and make other predictions based on known links between genes and diseases. However, genetic tests have yet to become a routine part of medical care, in part because there is not enough evidence to show they help improve patients' health. The Institute of Medicine (IOM) held a workshop to explore how researchers can gather better evidence more efficiently on the clinical utility of genetic tests. Generating Evidence for Genomic Diagnostic Test Development compares the evidence that is required for decisions regarding clearance, use, and reimbursement, to the evidence that is currently generated. The report also addresses innovative and efficient ways to generate high-quality evidence, as well as barriers to generating this evidence. Generating Evidence for Genomic Diagnostic Test Development contains information that will be of great value to regulators and policymakers, payers, health-care providers, researchers, funders, and evidence-based review groups.

Effects of Psychoactive Chemicals on Commercial Driver Health and Performance: Stimulants, Hypnotics, Nutritional, and Other Supplements - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2011)
TRB2019s Commercial Truck and Bus Safety Synthesis Program (CTBSSP) Synthesis 19: Effects of Psychoactive Chemicals on Commercial Driver Health and Performance: Stimulants, Hypnotics, Nutritional, and Other Supplements identifies available information and research gaps relating to the use of chemical substances by commercial drivers and is intended to provide up-to-date information to inform decision makers about the near-, mid-, and long-range planning needs for research and educational outreach programs.The report is designed to help the commercial transportation safety community and the Federal Motor Carrier Safety Administration in addressing issues involving the proliferation and availability of psychoactive chemical substances.Appendixes D and G to CTBSSP Synthesis 19 are available only in the pdf version of report.

Long-Term Health Consequences of Exposure to Burn Pits in Iraq and Afghanistan - Institute of Medicine
Many veterans returning from the conflicts in Iraq and Afghanistan have health problems they believe are related to their exposure to the smoke from the burning of waste in open-air \

Explaining Divergent Levels of Longevity in High-Income Countries - National Research Council (The National Academies Press, 2011)
During the last 25 years, life expectancy at age 50 in the United States has been rising, but at a slower pace than in many other high-income countries, such as Japan and Australia. This difference is particularly notable given that the United States spends more on health care than any other nation. Concerned about this divergence, the National Institute on Aging asked the National Research Council to examine evidence on its possible causes. According to Explaining Divergent Levels of Longevity in High-Income Countries, the nation's history of heavy smoking is a major reason why lifespans in the United States fall short of those in many other high-income nations. Evidence suggests that current obesity levels play a substantial part as well. The book reports that lack of universal access to health care in the U.S. also has increased mortality and reduced life expectancy, though this is a less significant factor for those over age 65 because of Medicare access. For the main causes of death at older ages2014cancer and cardiovascular disease2014available indicators do not suggest that the U.S. health care system is failing to prevent deaths that would be averted elsewhere. In fact, cancer detection and survival appear to be better in the U.S. than in most other high-income nations, and survival rates following a heart attack also are favorable. Explaining Divergent Levels of Longevity in High-Income Countries identifies many gaps in research. For instance, while lung cancer deaths are a reliable marker of the damage from smoking, no clear-cut marker exists for obesity, physical inactivity, social integration, or other risks considered in this book. Moreover, evaluation of these risk factors is based on observational studies, which2014unlike randomized controlled trials2014are subject to many biases.

Climate Change, the Indoor Environment, and Health - Institute of Medicine (The National Academies Press, 2011)
The indoor environment affects occupants' health and comfort. Poor environmental conditions and indoor contaminants are estimated to cost the U.S. economy tens of billions of dollars a year in exacerbation of illnesses like asthma, allergic symptoms, and subsequent lost productivity. Climate change has the potential to affect the indoor environment because conditions inside buildings are influenced by conditions outside them. Climate Change, the Indoor Environment, and Health addresses the impacts that climate change may have on the indoor environment and the resulting health effects. It finds that steps taken to mitigate climate change may cause or exacerbate harmful indoor environmental conditions. The book discusses the role the Environmental Protection Agency (EPA) should take in informing the public, health professionals, and those in the building industry about potential risks and what can be done to address them. The study also recommends that building codes account for climate change projections; that federal agencies join to develop or refine protocols and testing standards for evaluating emissions from materials, furnishings, and appliances used in buildings; and that building weatherization efforts include consideration of health effects. Climate Change, the Indoor Environment, and Health is written primarily for the EPA and other federal agencies, organizations, and researchers with interests in public health; the environment; building design, construction, and operation; and climate issues.

Child and Adolescent Health and Health Care Quality: Measuring What Matters - Institute of Medicine; National Research Council (The National Academies Press, 2011)
Increasing public investments in health care services for low-income and special needs children and adolescents in the United States have raised questions about whether these efforts improve their health outcomes. Yet it is difficult to assess the general health status and health care quality for younger populations, especially those at risk of poor health outcomes, because the United States has no national information system that can provide timely, comprehensive, and reliable indicators in these areas for children and adolescents. Without such a system in place, it is difficult to know whether and how selected health care initiatives and programs contribute to children's health status. Child and Adolescent Health and Health Care Quality identifies key advances in the development of pediatric health and health care quality measures, examines the capacity of existing federal data sets to support these measures, and considers related research activities focused on the development of new measures to address current gaps. This book posits the need for a comprehensive strategy to make better use of existing data, to integrate different data sources, and to develop new data sources and collection methods for unique populations. Child and Adolescent Health and Health Care Quality looks closely at three areas: the nature, scope, and quality of existing data sources; gaps in measurement areas; and methodological areas that deserve attention. Child and Adolescent Health and Health Care Quality makes recommendations for improving and strengthening the timeliness, quality, public transparency, and accessibility of information on child health and health care quality. This book will be a vital resource for health officials at the local, state, and national levels, as well as private and public health care organizations and researchers.